Handbook of ancient Afro-Eurasian economies. Volume 2: Local, regional, and imperial economies - Sitta von Reden (De Gruyter Oldenbourg, 2022)
In the second volume a wide range of economic actors - from kings and armies to cities and producers - are discussed within different imperial settings as well as the tools which enabled and constrained economic outcomes. A central focus are nodes of consumption that are visible in the archaeological and textual records of royal capitals, cities, religious centers, and armies that were stationed in imperial frontier zones.
Keywords: 330; Extractive economies; imperial frontier zones; agrarian development